Empowerment of Housewives through Activities of Processing Coconut into Flower Pots at Palakka District - Asmah Amir; Andi Hajar; Fatmawati Ramli; Sitti Asmah (International Journal of Community Engagement Payungi, 2022)
This community service program aims to increase community creativity in utilizing the natural resources available in the surrounding environment into useful and beneficial things, especially for the people in Tanah Tengah Village, Palakka District. The strategy used to achieve this goal is through a series of activities starting with field observations, conducting interviews and approaches to housewives who love ornamental plants (flowers), directing them to collect coconut husks around them so that later they can processed into useful things and reduce spending on buying flower pots that are displayed in various places, especially in the market. In addition, increasing creativity in processing coconut coir into flower pots can make local communities have space to open businesses in increasing economic income for the welfare of families and communities so that later they need continuous assistance to produce products that are of interest to various groups of people (taking into account the feasibility of being used as a business). ). Marketing activities are carried out by advertising products on various social media that are needed at all home scales with various product displays (mats and coconut fiber ropes, etc.) that are friendly to the environment and good for the growth of various ornamental plants, especially orchids and open-pore plants.